Photosynthetic features, growth, and yield of Thai Jasmine Rice as influenced by saline sol treated with organic matter - Cha-um, Suriyan; Kirdmance, Chalermpol (2011)
The study determined the effect of saline soil amended with organic matter (OM) on the photosynthetic characteristics, growth and productivity of Thai jasmine rice. Photosynthetic pigments, chlorophyll fluorescence, net photosynthetic rate (Pr), various growth parameters and yield were measured. Chlorophyll b, total chlorophyll and total carotenoid contents in the leaf tissues of rice grown in non-saline soil applied with OM were enriched better than in soil without OM. Degradation of photosynthetic pigments depended on the level of salinity. Chlorophyll a content and total chlorophyll content were positively related to maximum quantum yield of PSIl (Fy Fm) and quantum efficiency of PSII (Opsn), respectively. Moreover, photosynthetic efficiencies, as indicated by si and Pn, as well as plant height and yield traits, increased with addition of OM at increasing salt levels. The use of OM in Thai jasmine rice production is an effective method in solving the problem of saline soil.
Keywords: Rice yields; Rice varieties